Analysis and Design of the Attil's Waterworks - Jallad, Hossni; Ameed Heshme; Alaa Demide; Hisham Hamad (My University, 2018)
Water distribution systems play a vitally important role in preserving and providing a desirable life quality to the public. It has been in the past that much of the effort in the design of water distribution systems emphasizes on the aspect of least cost. The amount of effort and attention given to develop a procedure for system performance reliability evaluation has not attained a comparable scale. Realizing the fact that many of the aged infrastructures in our communities, including a water distribution system, have been deteriorated to the point that their service abilities have drawn much attention. There has been a growing awareness that it is equally important to have a public water distribution system possessing a high service reliability. There is very little work done in attempting to quantify the system reliability of a water distribution network An old water distribution network in Attil town was designed since 1984 and so it is to be studied and analyzed to identify the problems if it is existed and if needed redesign to be able to determine the volume of water needed by the residents of the town .And considering the population growth after 30 years to determine the demand and achieving adequate amount of water , because the number of residence has increased in the last years in attil town ,and their needs of water have been increased too . And this project is to be studied through employing engineering principles of analysis and design to the network by collecting data for current network using software such as WaterCad .